THE INVESTMENT OF MIGRANT WOMEN IN SECOND LANGUAGE LEARNING: A SYSTEMATIC REVIEW - Dang Arif Hartono; Phuong Lan Nguyen (JALL (Journal of Applied Linguistics and Literacy), 2022)
Migrant women, especially married migrant women, are perhaps one of the least discussed groups in the field of second language acquisition. To date, there have been limited studies on this group of learners. This is unfortunate because our inability to understand this group would restrict us from catering to their language learning needs. Because of this reason, we decided to conduct a systematic review to understand what the literature has revealed about their investment in language learning and how gender influences their decision to learn a second language. An in-depth review of 24 empirical studies published from 1995 to 2021 reveals that the new living conditions affect their self-positioning in family and society, gendered identities play a critical role in making a woman invest or not to invest in learning a second language, and gendered identities relevant to their family roles (e.g. being a mother or a wife) appear to be the most common and powerful factors in deciding their investment in learning a second language.Keywords: migrant women, language learning, motivation, investment